IL6/STAT3 axis mediates resistance to BRAF inhibitors in thyroid carcinoma cells. (1st October 2018) - Notarangelo, Tiziana; Sisinni, Lorenza; Trino, Stefania; Calice, Giovanni; Simeon, Vittorio; Landriscina, Matteo
Abstract: Thyroid carcinomas (TCs) bearing BRAF mutations represent approximately 26–53% of human thyroid malignancies and, differently from melanomas, are poorly sensitive to BRAF inhibitors (BRAFi), and develop acquired resistance through activation of alternative signaling pathways. A whole-genome gene expression analysis of TC BRAF V600E cells exposed to PLX4032 identified JAK/STAT among the most significantly modulated signaling pathways. Interestingly, both transient exposure and chronic adaptation to PLX4032 resulted in upregulation of IL6/STAT3 axis and this impaired the cytostatic activity of PLX4032. Mechanistically, exposure to PLX4032 enhanced IL6 secretion and this, in turn, was responsible for STAT3 upregulation, activation of ERK signaling and poor sensitivity to BRAF inhibition. Consistently, the dual blockade of STAT3 (by siRNA or pharmacological inhibition) or IL6 signaling (by the humanized anti-human IL6 receptor antibody, tocilizumab) and BRAF (by PLX4032) improved the inhibition of cell cycle progression compared to PLX4032 single agent. These data support the role of IL6/STAT3 signaling pathway in modulating TC cell response to PLX4032 and candidate IL6 targeting as a strategy to improve the activity of PLX4032 in BRAF V600E TC cells. Highlights: Both transient exposure and chronic adaptation to PLX4032 resulted in upregulation of IL6/STAT3 axis. The dual blockade of STAT3 or IL6 and BRAF improved the inhibition of cell cycle progression compared to PLX4032. Our data candidate IL6 targeting as a strategy to improve the activity of PLX4032 in BRAF V600E TC cells.